Effect of the Early Start Denver Model on Children With Autism Spectrum Disorder Syndrome of Different Traditional Chinese Medicine Types in Northeast China - Wang, Lili; Feng, Junyan; Zhang, Yu; Wang, Tiantian (Frontiers in Pediatrics, 2022)
Background:The clinical presentation of children with autism spectrum disorder (ASD) is heterogeneous, and there are little data available on the treatment of children with different types of ASD. We sought to explore which traditional Chinese medicine (TCM) syndrome type was more effective for children with ASD after 3 months of Early Denver Model intervention and to analyze the reasons for its efficacy from the perspective of TCM. Methods:This was a retrospective study. The subjects were children with ASD who were first diagnosed at the Developmental Behavioral Pediatrics, the First Hospital of Jilin University,between December 2018 to September 2019.Eighty-nine children were divided into a kidneyjing deficiency group, a liver qi stagnation group (LQ group), and a group with deficiency of both the heart and spleen. Results:After treatment, the total Autism Behavior Checklist(ABC), Autism Treatment Evaluation Checklist, and Childhood Autism Rating Scale scores were significantly reduced in the three groups (p< 0.05)compared to before treatment.Significant improvements were seen in all five domains of the Griffiths Development Scales-Chinese version in the LQ group (p< 0.05).After intervention, the LQ group showed greater improvements compared to the other two groups in the language, eye–hand coordination,body and object use,social and self-help, and total ABC scores. Conclusion:Our study showed that Early Denver Model intervention is effective in the treatment of three syndrome types of children with ASD, with the LQ group experiencing the most significant effects.